Assessment of the hemogram parameters in patients with paroxysmal supraventricular tachycardia: a retrospective study - Cosgun,Mehmet (2020)
SUMMARY OBJECTIVE: Inflammation has been suggested as a potential mechanism in the pathogenesis of arrhythmia. Hemogram parameters such as monocyte count to high-density lipoprotein cholesterol ratio (MHR), neutrophil/lymphocyte ratio (NLR), and monocyte/lymphocyte ratio (MLR) have been considered to be markers of inflammation and new cardiovascular risk predictors. This retrospective study aimed to investigate the relationship between MHR, NLR, and MLR in patients with paroxysmal supraventricular tachycardia (PSVT). METHODS: A retrospective study conducted at a university hospital in Bolu, Turkey, between 2017 and 2019. Our study included 196 patients who underwent electrophysiological study (EPS) due to palpitation or documented PSVT on electrocardiography (ECG). Patients having documented atrioventricular nodal re-entrant tachycardia (AVNRT) on ECG or inducible AVNRT on EPS were included in the PSVT group (n=130), and patients with palpitation but without inducible arrhythmia on EPS (n=66) were included in the control group. Routine biochemical and hemogram tests were performed before the EPS procedure. RESULTS: When hemogram parameters were compared, there was no statistically significant difference in MHR values [0.010 (0.001-0.030) vs 0.010 (0.001-0.020) p =0.67]. Additionally, both NLR [2.21(0.74-11.36) vs 1.98(0.72-24.87) p=0.13] and MLR [0.25 (0.03-1.05) vs 0.24(0.07-1.39) p=0.41] were not statistically significant between the two groups. CONCLUSION: There is no significant difference in PSVT patients regarding hemogram parameters including white blood cell subtypes, MLR, NLR, and MHR. Therefore the evaluation of hemogram parameters may not be clinically relevant for PSVT patients.